Neglected plants of Prunus L. (Rosaceae) in East China - Li, Jun-Ping; Chen, Feng; Xie, Wen-Yuan; Wang, Jun-Feng; Mao, Li-Mi; Ying, Shang-Jiao; Chen, Zheng-Hai; Lou, Jia; Jin, Xiao-Feng (Phytotaxa, 2024)
A new species with a new variety of Prunus L. (Rosaceae) from Zhejiang, East China, namely P. huadongensis, and P. huadongensis var. pubipes, were described and illustrated. Prunus huadongensis is similar to P. conradinae Koehne, but differs in having leaf blades glabrous on both surfaces, margin obtusely serrulate, teeth curved-inward with a breast-like apical gland, and pedicel apically slightly thickened. Additionally, pollen sculpture of P. huadongensis is characterized by relatively coarse striae and no distinctive perforations between striate elements, whereas pollen sculpture of P. conradinae shows fine striae and dense perforations between striate elements. The new variety, var. pubipes, differs from the typical variety in leaf blades appressed-pubescent on veins of abaxial surfaces, branchlets, petioles, peduncles, pedicels, outside base of hypanthium and sepals all spreading-pubescent, leaf blade obtusely biserrulate at margin.